Validation of the Malay version of the snyder hope scale among Malaysian cancer patients - Mohammad Farris Iman Leong Abdullah,; Rohayu Hami,; Noorsuzana Mohd Shariff,; Siti Shahanis Md Sharif,; Gokula Kumar Appalanaido,; Nizuwan Azman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Hope leads to lower depression and anxiety and is associated with improved quality of life of cancer patients. In this study, Hope Scale (HS) was translated into Malay, and the psychometric properties of the Malay version of the Hope Scale were investigated among Malaysian cancer patients. Concurrent translation and back translation of the original English version of the Hope Scale were performed, and the Malay version was administered to 195 cancer patients with different cancer diagnoses at baseline assessment and 2 months later at follow-up. The Hope Scale (Malay) total score (Cronbach’s α = 0.72; intraclass correlation coefficient (ICC) = 0.67) and its domains (Cronbach’s α [pathway] = 0.7; Cronbach’s α [agency] = 0.7; ICC[Pathway] = 0.64; ICC[Agency] = 0.70) demonstrated acceptable internal consistencies and test-retest reliability. Convergent and discriminant validities were also achieved by the Hope Scale (Malay). The Hope Scale (Malay) demonstrated construct validity, as confirmatory factor analysis demonstrated that the items in the Hope Scale (Malay) best fit into two domains, which was true for the original English version. The Hope Scale (Malay) had acceptable psychometric properties and thus is suitable for assessing hope in Malaysian cancer patients.